Studying Customer Satisfaction with Service Quality Using the Servqual Method: Case Study at PT. Federal International Finance East Surabaya Branch - Mahjudin Mahjudin; Muchammad Ilham Syaifullah A. M; Naurah Aurelia M (Digital Innovation : International Journal of Management, 2024)
The research for this thesis is entitled: "Customer Satisfaction Analysis of PT Service Quality. Federal International Finance East Surabaya Branch Using the Servqual Method.” The purpose of this research is to determine the quality of services provided at PT. Federal International Finance East Surabaya Branch towards all customers seen from the 5 dimensions of service and to find out the efforts made to improve service quality at PT. Federal International Finance East Surabaya Branch to retain customers. The analytical tool used in this research uses the Servqual method. From the research results, it is known that the gap for the Physical Evidence dimension has a gap value in the third item of -0.08, namely that employees look neat & professional. The reliability dimension has a gap value in the first, fourth and fifth items, namely if an employee promises to do something within a certain time period, then they actually carry it out at -0.06, employees provide services according to the promised time at -0.46 , and FIFGROUP keeps its data error-free by -0.40. The responsiveness dimension has a gap value in the first and third items, namely that employees will tell customers exactly when service will be provided at -0.04, and employees are always willing to help customers who come at -0.12. The guarantee dimension has a gap value in the second item, namely that customers will feel safe when making transactions of -0.04.